2013
DOI: 10.1007/s10508-013-0191-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation During Sex and Sexual Arousal in Women With and Without a History of Childhood Sexual Abuse

Abstract: Women with a history of childhood sexual abuse (CSA) experience dissociative symptoms and sexual difficulties with greater frequency than women without a history of CSA. Current models of sexual dysfunction for sexual abuse survivors suggest that dissociation may mediate the relationship between CSA and sexual arousal difficulties. Dissociation, however, is often conceptualized as a single construct in studies of CSA and not as separate domains as in the dissociation literature. In the present study, women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 63 publications
2
19
1
Order By: Relevance
“…Whilst numerous strategies were suggested for managing intrusive experiences during sex, few of these had been empirically validated. Ten studies were identified that recommended strategies, of which one empirically tested the strategy (although this was not specific to PTSD; Brotto, Seal, & Rellini, ), eight provided anecdotal clinical protocols (Ainscough & Toon, ; Ashton, ; Dolan, ; Glantz & Himber, ; Kennerley, ; Maltz, ; Sanderson, ; Webster, ), and one was a suggestion that emerged from a primary research study (Bird, Seehuus, Clifton, & Rellini, ). We identified the following strategies for sexual problems following trauma (the number of sources recommending each strategy is in brackets): Information about antecedents (e.g., psychosexual education, identifying triggers) (6); avoidance/reducing exposure to cues (e.g., varying positions, removing triggers) (6); past–present contextual discrimination or grounding (e.g., attention training) (5); sensate focus/mindfulness (5); including partner in therapy (5); setting boundaries with partner (4); relaxation (3); cognitive reframing/restructuring (2); and reclaiming sex as something positive (2).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst numerous strategies were suggested for managing intrusive experiences during sex, few of these had been empirically validated. Ten studies were identified that recommended strategies, of which one empirically tested the strategy (although this was not specific to PTSD; Brotto, Seal, & Rellini, ), eight provided anecdotal clinical protocols (Ainscough & Toon, ; Ashton, ; Dolan, ; Glantz & Himber, ; Kennerley, ; Maltz, ; Sanderson, ; Webster, ), and one was a suggestion that emerged from a primary research study (Bird, Seehuus, Clifton, & Rellini, ). We identified the following strategies for sexual problems following trauma (the number of sources recommending each strategy is in brackets): Information about antecedents (e.g., psychosexual education, identifying triggers) (6); avoidance/reducing exposure to cues (e.g., varying positions, removing triggers) (6); past–present contextual discrimination or grounding (e.g., attention training) (5); sensate focus/mindfulness (5); including partner in therapy (5); setting boundaries with partner (4); relaxation (3); cognitive reframing/restructuring (2); and reclaiming sex as something positive (2).…”
Section: Discussionmentioning
confidence: 99%
“…Survivors may also have severe responses to any sexual contact, including touch, kissing, nudity, flirting, and initiations of sexual behavior (including manual, oral, or genital stimulation and/or intercourse), which can become triggering reminders of the trauma. Viewing sexual difficulties through this trauma conceptualization can help explain commonly reported sexual concerns among sexual trauma survivors, such as low sexual desire, sexual arousal problems, pain during sex, difficulty with orgasm, difficulty experiencing pleasure, emotional and behavioral avoidance, and dissociative symptoms (Bird, Seehus, Clifton, & Rellini, ; O'Driscoll & Flanagan, 2016; Rellini, ).…”
Section: The Effects Of Sexual Traumamentioning
confidence: 99%
“…That change is interpreted as increased physiological genital sexual arousal. Although research finds equivalent levels of self-reported subjective sexual arousal between women with and without a history of SV (Gilmore et al, 2010; Rellini & Meston, 2011), findings on differences in vaginal vasocongestion are somewhat mixed with most studies finding attenuation of VPA in women with a history of SV (Gilmore et al, 2010; Rellini et al, 2012; Rellini & Meston, 2006; Rellini, Hamilton, Delville, & Meston, 2009; Schacht et al, 2007) and others showing no differences (Bird, Seehuus, Clifton, & Rellini, 2013; Rellini & Meston, 2011). Sexual arousal has been shown to have a curvilinear relationship with sympathetic nervous system activity (Lorenz, Harte, Hamilton, & Meston, 2012).…”
Section: Measurement Of Sexual Arousalmentioning
confidence: 98%